Extending Investigations of miR‐126‐5p on the Regulation of CYP2A6, the Major Nicotine‐Inactivating Enzyme - Weilong Gu; Alec W. R. Langlois; Haidy Giratallah; Katrina G. Claw; Bhagwat Prasad; Kenneth E. Thummel; Rachel F. Tyndale (Pharmacology Research & Perspectives)
ABSTRACT CYP2A6 is the hepatic enzyme responsible for the metabolic inactivation of nicotine. Variation in CYP2A6 alters nicotine clearance, affecting numerous smoking behaviors and tobacco‐related diseases, making investigating sources of variation important. A published molecular study of microRNA‐126‐5p, the microRNA‐126 functional arm, showed it decreased CYP2A6 expression post‐transcriptionally; it also showed that higher CYP2A7 mRNA competed for microRNA‐126‐5p binding, mitigating the CYP2A6 reduction. To extend these observations, we investigated relationships between microRNA‐126‐5p and CYP2A6 protein and activity using a large human liver bank (n = 282). MicroRNA‐126‐5p was not inversely correlated with CYP2A6 protein (rs = 0.04, p > 0.05), nor was it significant in an unadjusted regression model (p > 0.05) or in an adjusted model (with genotype, age, and sex) (p > 0.05). Although CYP2A7 mRNA was positively correlated with CYP2A6 protein (rs = 0.48, p < 0.001), adding CYP2A7 mRNA to the adjusted model did not alter the relationship between microRNA‐126‐5p and CYP2A6 protein (p > 0.05), nor did CYP2A7 mRNA interact with microRNA‐126‐5p on CYP2A6 (p > 0.05). Similar results were found in modeling CYP2A6 activity. MicroRNA‐21 was used as a positive control (inversely correlated with CYP2A6 protein, rs = −0.33, p < 0.001) and microRNA‐152 as a negative control (not correlated with CYP2A6 protein, rs = −0.06, p > 0.05). These data do not support a role for microRNA‐126‐5p in downregulating CYP2A6 protein or activity, or for CYP2A7 mRNA in playing a decoy role, even when other predictors (genotype, age, and sex) were included in the model.